2013
DOI: 10.1108/00400911311309314
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial motivations and intentions: investigating the role of education major

Abstract: PurposeThe purpose of this study is to explore the difference in entrepreneurial intentions, perceived entrepreneurial motivation, and cognitive profiles (attitudes towards entrepreneurship, perceived behaviour control, and subjective norms) between individuals who have participated in enterprise education programmes in the universities and those who have not. The paper also investigates the mediating role of attitudes towards entrepreneurship, perceived behaviour control, and subjective norms related to entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
220
1
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(295 citation statements)
references
References 44 publications
32
220
1
18
Order By: Relevance
“…By knowing this, universities, government, or other parties who have a concern on entrepreneurial education, may design an entrepreneurial programs to attract students to be a young entrepreneur. Many studies showed that entrepreneurial education increased students' motivation and intention to be an entrepreneur (Bellotti et al, 2014;Duval-Couetil, 2013;Karimi, Biemans, Lans, Chizari, & Mulder, 2014;Piperopoulos & Dimov, 2014;Solesvik, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By knowing this, universities, government, or other parties who have a concern on entrepreneurial education, may design an entrepreneurial programs to attract students to be a young entrepreneur. Many studies showed that entrepreneurial education increased students' motivation and intention to be an entrepreneur (Bellotti et al, 2014;Duval-Couetil, 2013;Karimi, Biemans, Lans, Chizari, & Mulder, 2014;Piperopoulos & Dimov, 2014;Solesvik, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the topic often focus on Science, Technology, Engineering and Math (STEM) studies and careers, but just as Frome and Eccles (1998) include English in their study, we feel that the non-STEM fields would provide benefit if they were also investigated. In fact, a strong link has been demonstrated between parents' entrepreneurial activities and the likelihood of their children pursuing entrepreneurship (Carr & Sequeira, 2007;Solesvik, 2013;Van Auken, Stephens, Fry, & Silva, 2006). Our central theme aligns well with the published research on the topic.…”
Section: Impactsupporting
confidence: 82%
“…We measured Perceived Behavioral Control using three questions from Ajzen (2002) as cited in Solesvik (2013) ("If I wanted to, I could easily become an entrepreneur", "As an entrepreneur I would have sufficient control over my business", "It is entirely up to me whether or not I become an entrepreneur"). Question "PBC3" from Solesvik (2013) was left out per Solesvik (2013). We believe that Perceived Behavioral Control is an important topic for research in this field, connected to self-efficacy, but it appeared that many students reported high self-efficacy impressions regarding entrepreneurship in spite of having little experience being entrepreneurs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations